Different Mismatch Concepts for Magnetic Resonance Imaging–Guided Thrombolysis in Unknown Onset Stroke. Issue 6 (20th April 2020) - Scheldeman, Lauranne; Wouters, Anke; Boutitie, Florent; Dupont, Patrick; Christensen, Soren; Cheng, Bastian; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Gerloff, Christian; Muir, Keith W.; Nighoghossian, Norbert; et al.
Abstract : Objective: To explore the prevalence of the perfusion‐weighted imaging (PWI)–diffusion‐weighted imaging (DWI) mismatch and response to intravenous thrombolysis in the WAKE‐UP trial. Methods: We performed a prespecified post hoc analysis of ischemic stroke patients screened for DWI–fluid‐attenuated inversion recovery (FLAIR) mismatch in WAKE‐UP who underwent PWI. We defined PWI‐DWI mismatch as ischemic core volume < 70ml, mismatch volume > 10ml, and mismatch ratio > 1.2. Primary efficacy end point was a modified Rankin Scale score of 0–1 at 90 days, adjusted for age and symptom severity. Results: Of 1, 362 magnetic resonance imaging–screened patients, 431 underwent PWI. Of these, 57 (13%) had a double mismatch, 151 (35%) only a DWI‐FLAIR mismatch, and 54 (13%) only a PWI‐DWI mismatch. DWI‐FLAIR mismatch was more prevalent than PWI‐DWI mismatch (48%, 95% confidence interval [CI] = 43–53% vs 26%, 95% CI = 22–30%; p  < 0.0001). Screening for either one of the mismatch profiles resulted in a yield of 61% (95% CI = 56–65%). Prevalence of PWI‐DWI mismatch was similar in patients with (27%) or without (24%) DWI‐FLAIR mismatch ( p = 0.52). In an exploratory analysis in the small subgroup of 208 randomized patients with PWI, PWI‐DWI mismatch status did not modify the treatment response ( p for interaction = 0.73). Interpretation: Evaluating both the DWI‐FLAIR and PWI‐DWI mismatch patterns in patients with unknown time of stroke onset will result in the highest yield of thrombolysis treatment. The treatment benefit of alteplase in patients with a DWI‐FLAIR mismatch seems to be driven not merely by the presence of a PWI‐DWI mismatch, although this analysis was underpowered. ANN NEUROL 2020;87:931–938